2020
DOI: 10.3390/ma13020272
|View full text |Cite
|
Sign up to set email alerts
|

AFM Analyses of 3XXX Series Al Alloy Reinforced with Different Hard Nanoparticles Produced in Liquid State

Abstract: In the present work, nanocomposites-based 3XXX series Al alloy with three different types of hard nanoparticles, including TiO2, C, and CeO2, were produced employing two techniques such as mechanical milling and stir-casting method in order to evaluate the viability of integration of the reinforcement in the Al matrix. The integration and dispersion capability of the reinforcement into the Al alloy (3xxx Series) matrix was evaluated, using a phase angle difference and surface roughness analyses by atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The increase of the mechanical properties of the composite with the milling time is related to several strengthening mechanisms: grain size refinement, powder surface area increases, crystallite size reduction, integration and dispersion of the reinforcing particle into the Al matrix, and strain hardening, among others [ 25 , 26 ]. From the results, we observed that an increase in sintering temperature and time also favored the precipitation and growth of second phases (e.g., Al 4 C 3 or AlCu,); this effect was observed in the contour plot for the yield stress and microhardness tests when the sintering time was increased from 1.5 to 3 h. The presence of these second phases has been previously reported in other works on X-ray diffraction analysis carried out on samples with C and Cu content [ 27 , 28 ]. The most significant effect was observed in the microhardness tests for 3/100 samples, where a change in sintering change from 1.5 to 3 h (at 600 °C hold) resulted in an increase of approximately ≈ 23% in the microhardness value; while, for the yield stress tests (under the same conditions), it presented an increase of ≈ 10% (see Figure 4 a,b).…”
Section: Discussionsupporting
confidence: 73%
“…The increase of the mechanical properties of the composite with the milling time is related to several strengthening mechanisms: grain size refinement, powder surface area increases, crystallite size reduction, integration and dispersion of the reinforcing particle into the Al matrix, and strain hardening, among others [ 25 , 26 ]. From the results, we observed that an increase in sintering temperature and time also favored the precipitation and growth of second phases (e.g., Al 4 C 3 or AlCu,); this effect was observed in the contour plot for the yield stress and microhardness tests when the sintering time was increased from 1.5 to 3 h. The presence of these second phases has been previously reported in other works on X-ray diffraction analysis carried out on samples with C and Cu content [ 27 , 28 ]. The most significant effect was observed in the microhardness tests for 3/100 samples, where a change in sintering change from 1.5 to 3 h (at 600 °C hold) resulted in an increase of approximately ≈ 23% in the microhardness value; while, for the yield stress tests (under the same conditions), it presented an increase of ≈ 10% (see Figure 4 a,b).…”
Section: Discussionsupporting
confidence: 73%